Respuestas
Respuesta dada por:
1
Yo lo hago en un paso, pero lo hare paso a paso:
F(x)=![(2x)^{ \frac{-1}{2} } (2x)^{ \frac{-1}{2} }](https://tex.z-dn.net/?f=%282x%29%5E%7B+%5Cfrac%7B-1%7D%7B2%7D+%7D)
1ra derivada
F¹(x)=![( \frac{-1}{2} )*(2x)^{- \frac{1}{2}-1 }*dy/dx(2x)=( \frac{-1}{2} )*(2x)^{ \frac{-3}{2} }*(2) ( \frac{-1}{2} )*(2x)^{- \frac{1}{2}-1 }*dy/dx(2x)=( \frac{-1}{2} )*(2x)^{ \frac{-3}{2} }*(2)](https://tex.z-dn.net/?f=%28+%5Cfrac%7B-1%7D%7B2%7D+%29%2A%282x%29%5E%7B-+%5Cfrac%7B1%7D%7B2%7D-1+%7D%2Ady%2Fdx%282x%29%3D%28+%5Cfrac%7B-1%7D%7B2%7D+%29%2A%282x%29%5E%7B+%5Cfrac%7B-3%7D%7B2%7D+%7D%2A%282%29)
F¹(x)=
RESP.
F(x)=
1ra derivada
F¹(x)=
F¹(x)=
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años